La religiosidad popular y el ecologismo de los pobres. Apuntes sobre el papel de la espiritualidad en los movimientos de resistencia (Revista Sapiência: sociedade, saberes e práticas educacionais (2238-3565), 2017)
Facing a bleak portrait of reality, in which environmental disaster, increased poverty, food crisis, hedonistic individualism and alienation are commonplace, religious communities are mobilizing to found ecological and economic alternatives. On the other hand, social movements in the Global South are generating egalitarian practices and ecological projects which need to be analysed. For this reason, the link between ecology and spirituality is not only an interesting topic for the social sciences, but also a vital aspect of our times. Thus, the study of ecological aspects within social movements of Latin America will contribute to a better understanding of the challenges presented by this new century. My goal is to analyse patterns and religious dimensions within Latin American social movements to better recognize their specificities and continuity. The article will focus on the role liberation theology has played since the second half of the 20th Century. By contrasting explanations based on research of green capitalism, I will expand upon the main thesis of the Latin American decolonisation thought process.